Efficacy and safety of Chinese herbal medicines combined with cyclophosphamide for connective tissue disease-associated interstitial lung disease: A meta-analysis of randomized controlled trials - Yin, Xietian; Zhao, Shichao; Xiang, Nan; Chen, Jidong; Xu, Jun; Zhang, Yudan (Frontiers in Pharmacology, 2023)
Objectives: To evaluate the effectiveness and safety of Chinese herbal medicines (CHMs) combined with cyclophosphamide (CTX) for connective tissue disease-associated interstitial lung disease (CTD-ILD) by performing a meta-analysis. Methods: We searched RCTs of Chinese herbal medicines therapy for connective tissue disease-associated interstitial lung disease in ten databases. Methodological quality assessment was performed by the Cochrane collaboration tool. RevMan v5.3 and Stata v14.0 software were used for performing data analysis. This study was conducted and reported following the PRISMA checklist. Results: Overall, seven RCTs with 506 participants were included for this analysis. Current data indicated that Chinese herbal medicines combined with cyclophosphamide contributed to a betterment in improving the clinical efficacy rate of connective tissue disease-associated interstitial lung disease [risk ratio (RR) = 1.21, 95% confidence interval (CI): (1.09, 1.35), p = 0.0003], tended to benefit improvement of lung function, which included VC [weighted mean difference (WMD) = 9.49, 95% CI: (5.54, 13.45), p < 0.00001], FVC [standardized mean difference (SMD) = 0.83, 95% CI: (0.36, 1.29), p = 0.0005], FEV1 [SMD = 0.54, 95% CI: (0.23, 0.86), p = 0.0008], TLC [SMD = 0.90, 95% CI: (0.68, 1.13), p < 0.00001], DLCO [SMD = 1.05, 95% CI: (0.38, 1.73), p = 0.002], and MVV [SMD = 0.83, 95% CI: (0.50, 1.17), p < 0.00001], and it also could significantly reduce the HRCT integral of lungs [SMD = −2.02, 95% CI: (−3.14, −0.91), p = 0.0004] and the level of ESR [WMD = −13.33, 95% CI: (−18.58, −8.09), p < 0.00001]. Furthermore, there was no statistical significance in the incidence of adverse events (AEs), which indicate that Chinese herbal medicines combined with cyclophosphamide is safe and does not increase adverse events compared with cyclophosphamide alone. Conclusion: Our analysis indicates that Chinese herbal medicines combined with cyclophosphamide may be a more effective strategy on the treatment of connective tissue disease-associated interstitial lung disease in the clinic. Because it included studies with relatively small sample size, the results need to be confirmed by more well-designed and large-scale RCTs. Systematic Review Registration:https://10.37766/inplasy2022.12.0010.